How do countries specialize in agricultural production? A complex network analysis of the global agricultural product space - Campi, Mercedes Maria (2020)
Using a complex-network perspective, this paper empirically explores the determinants of the process through which countries, given their capabilities, specialize in agricultural production. Using production data from the Food and Agriculture Organization (FAO) for the period 1993-2013, we characterize the agricultural production space as a time-sequence of bipartite networks, connecting countries to the agricultural products they produce. We then project this representation in the agricultural production spaces, linking countries or products according to their similarity in production profiles, and we identify properties and determinants underlying their evolution. We find that, despite the unprecedented pressure that food systems have been undergoing in recent years, the agricultural production space is a very dense network displaying well-defined and stable communities of countries and products. We also show that the observed country community structures are not only shaped by environmental conditions, but also by economic, socio-political, and technological factors. We conclude by discussing the implications of such findings on our understanding of the complex relationships involving production capabilities and specialization patterns.